(untitled) (International Journal of Engineering and Computer Science, 2018)
The significant health issues among the senior and old individuals are eye ailments. One of the most important internal components in eye is called retina. Retinal images play vital role in several applications such as disease diagnosis and human recognition. They also play a major role in early detection of diabetics by comparing the states of the retinal blood vessels. Retinal Image Analysis is a key element in detecting retinopathies in patients. Diabetic Retinopathy is one of the most common diabetic eye conditions which cause blindness induced by alterations in the blood vessels of the retina. In this work we detect the blood vessels effectively for the diagnosis of disease such as diabetes, glaucoma, and hemorrhage